Case reportAtypical teratoid/rhabdoid tumor of the brain in an adult with 22q deletion but no absence of INI1 protein: a case report and review of the literature - Jin, Shumei; Sun, Cuiyun; Yu, Shizhu; Wang, Qian; An, Tongling; Wen, Yanjun (Folia Neuropathologica, 2015)
We report a case of atypical teratoid/rhabdoid tumor (AT/RT) of the central nervous system (CNS) in an adult and its immunological phenotype and chromosomal DNA imbalance characteristics, as detected by comparative genomic hybridization (CGH). The immunohistochemical characteristics showed that atypical rhabdoid cells were positive for epithelial membrane antigen, vimentin, desmin, and glial fibrillary acidic protein, but there was no absence of INI1 protein. The CGH results identified the imbalances of the case to be the loss of 1p, 5q, 12q, 15q, 19q and 22q and the gain of 9q. Our discovery raises the question whether INI1 is implicated in all cases and whether its deletion is necessary in the pathogenesis of AT/RT, and also whether additional genetic pathways might exist. These data will offer useful information for further research on AT/RTs.